Fintech in islamic finance literature: A review - Posumah, Nurcahya Hartaty (Accounting Studies and Tax Journal (COUNT), 2024)
This literature review examines the role of fintech in the context of Islamic finance. Through a systematic analysis of relevant literature, this research highlights the contribution of fintech in improving Islamic financial services as well as the challenges faced in the integration process. These findings indicate that although fintech has opened the door to innovation in the Islamic finance industry, there is still a need to overcome barriers related to sharia compliance and consumer protection. Therefore, this research underlines the importance of a careful and planned approach in integrating fintech with Islamic finance principles.